A facile modular approach to the 2D oriented assembly MOF electrode for non-enzymatic sweat biosensors. Issue 14 (26th March 2018) - Wang, Zhengyun; Gui, Mengxi; Asif, Muhammad; Yu, Yang; Dong, Shuang; Wang, Haitao; Wang, Wei; Wang, Feng; Xiao, Fei; Liu, Hongfang
Abstract : The preparation of ordered metal organic frameworks (MOFs) will be a critical process for MOF-based nanoelectrodes in the future. Abstract : The preparation of ordered metal organic frameworks (MOFs) will be a critical process for MOF-based nanoelectrodes in the future. In this work, we develop a novel approach to fabricating a type of MOF electrode based on flexible amino-functionalized graphene paper modified with 2D oriented assembly of Cu3 (btc)2 nanocubes via facile interfacial synthesis and an effective dip-coating method. One interesting finding is that 2D arrays of Cu3 (btc)2 nanocubes at oil–water interfaces can be transferred on amino-functionalized graphene paper, leading to a densely packed monolayer of Cu3 (btc)2 nanocubes with a uniform size loaded on the paper electrode. The electrode demonstrates a variety of excellent sensing performances toward sweat lactate and glucose and has been applied in a non-enzymatic electrochemical biosensing platform for the first time. The modular nature of this approach to assembling MOF nanocrystals will provide new insight into the design of MOF-based electrodes for a wide range of applications in biosensing instruments, wearable electronics, and lab-on-a-chip devices.